Pengaruh Lama Perendaman terhadap Absorpsi Tetrasiklin pada Adsorben Limbah Sisik Ikan Gurami (Osphronemus Gouramy) - Sabrina M Pratama; Ghiza J.K. Barqly; Retno Widyastuti; Rizka N Wardani; Dear F Sielma; Al Munawir (Majalah Kedokteran Gigi Indonesia, 2015)
Influence of Immersion Length on Tetracycline Absorption on Gourami (Osphronemus Gouramy) Scales as Adsorbent. Gourami (Osphronemus Gouramy) scales are one of the natural sources of collagen. This fish scale’s collagen has functional properties, such as bio-degradable (easily decomposed), bio-compatible (compatible with surrounding tissue), and potential as bio-adsorbent. The absorbent properties of collagen are currently used as a transport material in local drug delivery for periodontal disease treatment, which is known as tetracycline chip. However, this chip is made of synthetic collagen so it is not absorbable by the body’s system. The price is also expensive. This study’s aim is to prove the potency of Gourami scales as a source of collagen in medical treatment, especially as a transport material of tetracycline for periodontal disease treatment. The gourami scale was obtained from seafood restaurant in Jember, Jawa Timur. About 500 mg of gourami scales was immersed into 20 ml tetracycline solution in beaker glass. About 200 μl solution from the beaker glass was taken with micropipette after 1-hour, 2-hour, 4-hour, 12-hour and 24-hour after immersed. After that, the solution was collected into an eppendorf for each time. The absorbance was measured with spectrophotometer at 450 nm wave length. This procedure was repeated five times. The lowest absorbance occured at 1-hour time (160,6 μg/μl). The result from light and inverted microscope examination shows a bond between collagen from gourami scales with tetracycline. Gourami scale has the ability to absorb the highest rate of tetracycline at 1-hour immersed time by forming a bond between collagen and tetracycline.